Stephtetrandrine A-D, bisbenzylisoquinoline alkaloids from Stephania tetrandra. Issue 2 (17th January 2023) - Yang, Li-Jun; Yang, Zhong-Duo; Li, Zhi-Jie; Yang, Shu-Hong; Shu, Zong-Mei
Abstract: Four undescribed bisbenzylisoquinoline alkaloids, designated as Stephtetrandrine A-D, were isolated from the roots of Stephania tetrandra . Their structures were elucidated by IR, HRESIMS, ECD spectra, 1 D and 2 D NMR spectra and comparison with the literature data. Additional five known compounds (limacine, tetrandrine, N - trans -Feruloyltyramine, 2′-N-chloromethyltetrandrine, 2, 2'-N-N-dichloromethyltetrandrine) were also isolated. N - trans -Feruloyltyramine was isolated from Stephania tetrandra for the first time. The isolated compounds were tested for monoamine oxidase, acetylcholinesterase, phosphoinositide 3-kinase α and human hepatoma cell HepG2 inhibitory activities. Stephtetrandrine C showed obvious inhibitory effect on human hepatoma HepG2, with IC50 value of 16.2 μM. Limacine and 2′-N-chloromethyltetrandrine showed moderate monoamine oxidase inhibitory effect with the IC50 values of 37.7 and 29.2 μM, respectively. Graphical Abstract: UF0001